2021
DOI: 10.3390/jcm10184047
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliability of the OMERACT Juvenile Idiopathic Arthritis Magnetic Resonance Scoring System for Temporomandibular Joints (JAMRIS-TMJ)

Abstract: Contrast-enhanced magnetic resonance imaging (MRI) remains the most comprehensive modality to assess juvenile idiopathic arthritis (JIA)-related inflammation and osteochondral damage in the temporomandibular joints (TMJ). This study tested the reliability of a new JIA MRI scoring system for TMJ (JAMRIS-TMJ) and the impact of variations in calibration and reader specialty. Thirty-one MRI exams of bilateral TMJs were scored independently using the JAMRIS-TMJ by 20 readers consisting of radiologists and non-radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(38 reference statements)
0
11
0
1
Order By: Relevance
“…This recommendation specifies “active” TMJ inflammation to differentiate from TMJ involvement without active inflammation (Table 1 ) ( 15 ). The use of JIA‐specific TMJ MRI protocols and scoring systems is recommended ( 22 , 23 , 24 , 25 ). It is recognized that the interpretation of MRI findings has an element of subjectivity and is influenced by the technique and equipment used for image capture, as well as by the expertise of the reader.…”
Section: Resultsmentioning
confidence: 99%
“…This recommendation specifies “active” TMJ inflammation to differentiate from TMJ involvement without active inflammation (Table 1 ) ( 15 ). The use of JIA‐specific TMJ MRI protocols and scoring systems is recommended ( 22 , 23 , 24 , 25 ). It is recognized that the interpretation of MRI findings has an element of subjectivity and is influenced by the technique and equipment used for image capture, as well as by the expertise of the reader.…”
Section: Resultsmentioning
confidence: 99%
“…MRI is currently regarded as the gold standard imaging technique for the evaluation of TMJ pathology, as it can accurately identify both the active and chronic arthritic sequelae ( 65 ). This opinion is based on reliable parameters in terms of sensitivity and specificity from numerous studies and systematic reviews of the literature ( 21 , 25 , 28 , 64 ); only the EULAR guidelines for JIA management recommend MRI for the diagnosis and follow-up evaluation of TMJ ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MRI is now regarded as the current imaging “gold standard” for the evaluation of inflammatory processes in TMJ pathology, as it can identify both active arthritis changes as well as arthritic sequelae, showing a moderate-to-good reliability ( 21 , 25 , 26 , 28 , 41 , 63 – 65 ).…”
Section: Methodsmentioning
confidence: 99%
“…Both closed- and open-mouth views can be performed for the optimal assessment of the mandibular condyle morphology, and the disc position and function, although recent studies have suggested that only closed-mouth views suffice. MRI scoring systems for TMJ involvement by JIA are available [ 57 , 58 , 59 ]. MRI definitely improved patient management, whereas US, despite efforts to prove its diagnostic relevance [ 60 , 61 ], has lagged behind: not only is US insensitive to small amounts of effusion and synovitis, it does not provide any information on BME when it may be the only pathology.…”
Section: Update In Magnetic Resonance Imagingmentioning
confidence: 99%